3-Dimensional Images of Mitral Annulus Perforation - Kumral Cagli, MD; Havva Tugba Gursoy, MD; Funda Basyigit, MD; Etga Koprucu, MD; Zehra Golbasi, MD (JACC: Case Reports, 2022)
In this clinical vignette, we describe a case of a patient with windsock-like posterior mitral annulus perforation at the site of annular calcification caused by infective endocarditis. Three-dimensional transesophageal images of the perforation resembling an “alien’s mouth” are very striking for how 3-dimensional imaging can improve visualization of anatomy of the heart. (Level of Difficulty: Intermediate.)